Bioremediation of polycyclic aromatic hydrocarbons in artificially contaminated soil / Nor Amani Filzah Mohd Kamil - Mohd Kamil, Nor Amani Filzah (2014)
Land used for industrial facilities or for waste disposal can be contaminated. Redevelopment of contaminated land often requires unacceptable risks are assessed and managed so that the site becomes suitable for its new use. One of the major criteria to be satisfied before such land can be reused is to ensure that remediation is carried out to remove all health hazards. One of the treatment methods that can be adopted involves bioremediation processes. Bioremediation process is considered to be environmentally sound and economically feasible. Other process, namely, physical and chemical processes require high energy, high costs and produce secondary contaminants that are more toxic if not completely degraded. This study is carried out to provide a better understanding on application of potential bacteria under non-indigenous condition, i.e., isolate from sludge and inoculate into contaminated soil. Many studies were conducted under indigenous and semi-indigenous condition. However, there are limited reports on studies under non-indiginous condition, particularly under aerobic condition. This study is also conducted to evaluate the effectiveness of potential bacteria and to established a mathematical model for PAHs biodegradation. The organic contaminants focus in this study is Polycyclic Aromatic Hydrocarbons (PAHs) and sand was selected as the soil media. PAHs are one of the most widespread organic contaminants and known to be highly toxic, mutagenic and carcinogenic. The objectives of this study are (i) a) establishment study parameters through characterization, (ii) biodegradation of PAHs, (iii) evaluation on effectiveness of PAHs biodegradation and (iv) model development. The methodology of this study consisted of four stages. The first stage involves determining the type of micropollutant that are present in the soil through characterization of soil taken from the Kubang Badak landfill. The second stage involves three phases of experimental works, namely, growth curve based on turbidity, biodegradation and survival of the strains in contaminated sand. The third stage involves five experimental works based on different factors, i.e., pH, temperature, phenanthrene concentration, bacteria number and heavy metals concentration. The final stage is to establish the kinetic parameter and the mathematical model for the biodegradation process. Results from stage 1 showed that phenanthrene is the most abundant PAHs in the soil samples, followed by anthracene. For heavy metals, zinc showed the highest mean concentration in the soil samples. Based on results in stage 2, a bacterial strain, namely, Corynebacterium uroalyticum isolated from municipal sludge shows the most potential as PAHs degrader. The evaluation of most potential strain is based on four factors, namely, day of inoculation, degradation rate, bacteria survival and degradation rate per colony. Results in stage 3 showed that the optimum condition occurred at pH 7, temperature of 30°C, initial phenanthrene concentration of 500 mg/kg, bacteria number of 109 cfu/g soil and samples without the addition of heavy metals. The final stage involve development of a mathematical model based on Monod kinetic. Kinetic parameters, qmax,X and Ks- qmax and Ks were observed to increase when the initial phenanthrene concentration increases. The Monod equation modified by Lawrence and McCarty (1970) was further enhanced in this study. As conclusion, understanding on application of potential PAHs degrading bacteria under nonindigenous condition has been evaluated in this study.